The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/asj.13098
|View full text |Cite
|
Sign up to set email alerts
|

Variations in fatty acid composition of Laoshan goat milk from partum to 135 days postpartum

Abstract: The objective of this study was to characterize the variations in fatty acid (FA) profile during 7 days of colostrum production and 5 months of mature milk production in Laoshan goats. The individual FA profiles of each sample were investigated by gas chromatography-mass spectrometry. Significant differences in FAs were found between colostrum and mature milk. The contents of saturated fatty acids (SFA), unsaturated fatty acids (UFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Literature comparing fatty acids of goat colostrum and milk is scarce. Lou et al [40] reported higher values of SFAs and lower values of MUFAs in milk than in colostrum of Laoshan breeds, which agreed with our results. Additionally, these latter authors [39] reported that the SFA proportion in colostrum ranged from 70% to 80%, in agreement with our results, while Marziali et al [41] reported that the SFA proportion in colostrum of Murciano-Granadina ranged from 48% to 58%.…”
Section: Milksupporting
confidence: 93%
See 1 more Smart Citation
“…Literature comparing fatty acids of goat colostrum and milk is scarce. Lou et al [40] reported higher values of SFAs and lower values of MUFAs in milk than in colostrum of Laoshan breeds, which agreed with our results. Additionally, these latter authors [39] reported that the SFA proportion in colostrum ranged from 70% to 80%, in agreement with our results, while Marziali et al [41] reported that the SFA proportion in colostrum of Murciano-Granadina ranged from 48% to 58%.…”
Section: Milksupporting
confidence: 93%
“…As reported by previous researchers [42,43], cis-and trans-C18:1 acids are often detected in goat milk, with a preeminent occurrence of C18:1 t11. However, from a sensory point of view, C8:0, C10:0 and 4-methyloctanoic fatty acids were the most influential in the flavor of milk and more predominant in caprine than in bovine or ovine milk [40,44]. Monomethyl-branched substitutions on short-chain fatty acids (C4-C6) are found only in goat milk and are implicated in goat-like flavors [45].…”
Section: Milkmentioning
confidence: 99%
“…The disease is characterized histologically steatosis and other parenchymal changes, ranging from inflammation to hepatocyte apoptosis/necrosis to fibrosis. NAFLD has become a globally occurring chronic disease that threatens the health of both humans and animals [20,21,96]. However, there is no efficacious drug available that can directly be used to treat NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Goat milk is widely used in dairy products because it is highly digestible, is hypoallergenic, and has high nutritional value (Lou et al, 2018;Chen et al, 2019a). The lower content of α S1 -casein and lactose in goat milk might allow β-LG and lactose to have better digestion and be less allergenic than cow milk (Bevilacqua et al, 2001;Lara-Villoslada et al, 2004;Chen et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%